2011
DOI: 10.5194/acp-11-8703-2011
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol particle number size distributions and particulate light absorption at the ZOTTO tall tower (Siberia), 2006–2009

Abstract: Abstract. This paper analyses aerosol particle number size distributions, particulate absorption at 570 nm wavelength and carbon monoxide (CO) measured between September 2006 and January 2010 at heights of 50 and 300 m at the Zotino Tall Tower Facility (ZOTTO) in Siberia (60.8 • N; 89.35 • E). Average number, surface and volume concentrations are broadly comparable to former studies covering shorter observation periods. Fits of multiple lognormal distributions yielded three maxima in probability distribution o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 63 publications
(74 reference statements)
5
27
0
Order By: Relevance
“…In the European, Asian and North American sectors there are two maxima: one in December-January and another in July. The summer peak is consistent with measurements of particle number and volume concentration in the planetary boundary layer at the Zotino Tall Tower Facility (ZOTTO) in the Siberian Low Arctic (60.8 • N, 89.35 • E), which show a June-July maximum in median particle number concentration (JuneJuly: 900 cm −3 ; November-February: 520 cm −3 ) and comparable volume concentrations between summer and winter (Heintzenberg et al, 2011). In the Atlantic sector, the seasonality is reversed with a summer minimum and a DecemberMarch maximum, corresponding to elevated sea salt aerosol concentrations generated by high winds during winter (see Sect.…”
Section: Pan-arctic Surface Extinction Maximum In Wintersupporting
confidence: 67%
“…In the European, Asian and North American sectors there are two maxima: one in December-January and another in July. The summer peak is consistent with measurements of particle number and volume concentration in the planetary boundary layer at the Zotino Tall Tower Facility (ZOTTO) in the Siberian Low Arctic (60.8 • N, 89.35 • E), which show a June-July maximum in median particle number concentration (JuneJuly: 900 cm −3 ; November-February: 520 cm −3 ) and comparable volume concentrations between summer and winter (Heintzenberg et al, 2011). In the Atlantic sector, the seasonality is reversed with a summer minimum and a DecemberMarch maximum, corresponding to elevated sea salt aerosol concentrations generated by high winds during winter (see Sect.…”
Section: Pan-arctic Surface Extinction Maximum In Wintersupporting
confidence: 67%
“…Measurements conducted at the ZOTTO site in central Siberia have shown that biogenic secondary organic aerosols reach high concentrations in summer and dominate the aerosol composition during this season (Mikhailov et al, 2015a, b;Ryshkevich et al, 2015). At this site, however, new particle formation events are seen much less frequently than at the Nordic stations (Heintzenberg et al, 2011). At present, relatively little is known about the overall contribution of biogenic emissions to aerosol number or mass concentrations, or to the cloud condensation nuclei budget, in northern Eurasia.…”
Section: Main Pollutantsmentioning
confidence: 98%
“…Continuous measurements of comprehensive sets of atmospheric constituents in the gas and particle phase together with meteorological parameters have been carried out at ZOTTO since October 2006 (Kozlova et al, 2008;Heintzenberg et al, 2008). With regards to aerosol, a study of the representativeness of the ZOTTO facility and first analyses of the particle size distribution data can be found in Heintzenberg et al (2008) and Heintzenberg and Birmili (2010); a statistical analysis of particle size distribution, particle absorption, and CO data taken from the first four years of operation of the ZOTTO facility (September 2006 to January 2010) is given in Heintzenberg et al (2011), together with seasonally dependent major air mass pathways and the related particle size distributions.…”
Section: Chi Et Al: Long-term Measurements Of Aerosol and Carbon mentioning
confidence: 99%
“…The principle of this instrument has been described previously (Knutson and Whitby, 1975;Winklmayr et al, 1991;Birmili et al, 1999) and detailed information about the ZOTTO DMPS system is given in Heintzenberg et al (2008Heintzenberg et al ( , 2011. In short, the ZOTTO DMPS consists of a 28 cm-long Hauke-type Differential Mobility Analyzer (DMA) and a Condensation Particle Counter (CPC, TSI model 3672).…”
Section: Size Distribution Measurementsmentioning
confidence: 99%